The effects of simulation-based education on initial neonatal evaluation and care skills - KARAKOÇ, AYŞE; BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (PROFESSIONAL MEDICAL PUBLICATIONS, 2019)
Objective: Neonatal evaluations performed at the very first minutes following postpartum are the most important steps in deciding for neonatal resuscitation. Therefore, the newborn initial care and evaluation notion and skills of midwives in the delivery hall are quite important. The study was planned to determine the effects of simulation education on newborn evaluation and care skills in midwifery students. Methods: This is a quasi-experimental study. The population of the study was composed of the 4th year students of Marmara University Faculty of Health Sciences (65 students in total), who selected the Intern Newborn course in the 2017-2018 Fall and Spring semesters. Results: The areas where the control group students did not apply at all or needed the help of the trainer were observed as delivery room preparation (86.2%), initial neonatal evaluation (96.6%) and registration/safety (69%). According to the Guide for Newborn Evaluation at the Delivery Room, the differences in the mean total scores and all sub-dimension scores were found to be significant in favor of the experiment group. Conclusion: Education programs that are carried out by computer-assisted simulation and in accordance with the teaching guide were effective on improvement of knowledge-skills on newborns' first evaluations in the delivery room.
Keywords: Checklists; Delivery room management; Midwifery student; Newborn evaluation; Professional practice evaluation; Simulation training; MIDWIFERY EDUCATION; EXPERIENCES